2016
DOI: 10.1016/j.ypmed.2016.07.029
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use among women of reproductive age: Impulsivity, cigarette smoking status, and other risk factors

Abstract: Introduction The study aim was to examine impulsivity and other risk factors for e-cigarette use among women of reproductive age comparing current daily cigarette smokers to never cigarette smokers. Women of reproductive age are of special interest because of the additional risk that tobacco and nicotine use represents should they become pregnant. Method Survey data were collected anonymously online using Amazon Mechanical Turk in 2014. Participants were 800 women ages 24–44 years from the US. Half (n = 400)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 49 publications
2
54
2
Order By: Relevance
“…Delay discounting of monetary rewards is a predictor of becoming a smoker among women of reproductive age [44] and moderated spontaneous quitting upon learning of pregnancy among lighter although not heavier smokers [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Delay discounting of monetary rewards is a predictor of becoming a smoker among women of reproductive age [44] and moderated spontaneous quitting upon learning of pregnancy among lighter although not heavier smokers [45]. …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the fact that nearly one third of current tobacco cigarette smokers also use e-cigarettes, a product for which nicotine levels and nicotine-related impurities have been shown to vary across brands (England et al, 2015), may be of concern if it results in a greater level of nicotine exposure during pregnancy. Alternatively, if e-cigarette use among pregnant smokers signals interest in smoking cessation, this could be leveraged to reduce the risk of nicotine exposure in this group (Chivers et al, 2016). However, considering that a higher proportion of current tobacco cigarette smokers were former e-cigarette users (44.5%) than current e-cigarette users (28.5%) whether pregnant smokers use e-cigarettes to reduce or quit smoking is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding internalizing disorders, depressive symptomatology is a well-established risk factor for tobacco use across the lifespan (Audrain-McGovern et al, 2009). Regarding externalizing disorders, the symptoms assessed on this subscale can be conceptualized as reflecting impulsivity, which is associated with cigarette smoking in both pregnant women (White, Redner, Skelly, & Higgins, 2014) and non-pregnant women of reproductive age (Chivers, Hand, Priest, & Higgins, 2016). On each subscale, participants earned one point for each item that they endorsed experiencing within the past year (range = 0–4 for internalizing and 0–5 for externalizing).…”
Section: Methodsmentioning
confidence: 99%
“…4 A survey study among women of reproductive age revealed that whereas impulsivity predicted e-cigarette use among never smokers, intention to quit smoking in the next 30 days and exhibiting higher nicotine dependence were important factors for e-cigarette use among current smokers. 4 A study of British smokers who had used e-cigarettes showed that initiation of e-cigarette use was influenced by social and psychological factors, such as using e-cigarettes with friends and family and the belief that e-cigarettes were less harmful than combustible cigarettes. 5 …”
mentioning
confidence: 99%